A preliminary survey of plant parasitic nematodes on carrots in Hai Duong province, Vietnam - Duyen, Nguyen Thi; Mai Linh, Le Thi; Tien, Nguyen Huu; Phap, Trinh Quang (Academia Journal of Biology, 2016)
Hai Duong province is the largest specialized area on the carrot production in Northern Vietnam. Recently, some papers reported about symptom of plant parasitic nematodes appeared in carrot cultivated areas, that causes damage to carrot production. i.e. both quantity and quality are decreased. Based on results of  the survey carried out in 2015 at two carrot planted areas, viz. Cam Giang and Nam Sach, Hai Duong province, 17 plant parasitic nematode species of 11 genera, 8 families and 3 orders of the parasitic nematodes, such as Tylenchida, Dorylaimida and Triplonchida were recorded. There are some differences on the specific composition as well as parasitic density of plant parasitic nematodes betweent carrot in Hai Duong and Lam Dong province. However, in both areas there are four parasitic groups appearred, viz. root-knot nematodes, lesion nematodes, root ectoparasitic nematodes and virrus vector nematodes. The presence of root-knot nematodes, lesion nematodes is related to damaged symptom in carot, such as multiple branched root, fork deformities (55.56%), root-knot (33.33%) and shorted root (5.56%).